Reflections by BASICS project advisory committee members - Emmanuel Okogbenin (AATF) - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2017)
Emmanuel Okogbenin (AATF), member of BASICS Project Advisory Committee speaking at the BASICS Annual review and planning meeting, ARPM.